Turkish University Students’ Perceptions of the World Wide Web as a Learning Tool: An Investigation Based on Gender, Socio-Economic Background, and Web Experience - Tekinarslan, Erkan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
The main purpose of the study is to investigate Turkish undergraduate students’ perceptions of the Web as a learning tool and to analyze whether their perceptions differ significantly based on gender, socio-economic background, and Web experience. Data obtained from 722 undergraduate students (331 males and 391 females) were used in the analyses. The findings indicated significant differences based on gender, socio-economic background, and Web experience. The students from higher socio-economic backgrounds indicated significantly higher attitude scores on the self-efficacy subscale of the Web attitude scale. Similarly, the male students indicated significantly higher scores on the self-efficacy subscale than the females. Also, the students with higher Web experience in terms of usage frequency indicated higher scores on all subscales (i.e., self-efficacy, affective, usefulness, Web-based learning). Moreover, the two-way ANOVA results indicated that the student’s PC ownership has significant main effects on their Web attitudes and on the usefulness, self-efficacy, and affective subscales.